Awareness of Dehydration and Health Effects Among People - A Survey - RUSKIN, PINKY; S, PREETHA; PRATHAP, LAVANYA (The journal of contemporary issues in business and government, 2020)
Water is a vital component in the body. Dehydration is defined as a decrease in water content in the body as a result of fluid loss or reduced water intake. Lack of hydration happens when the measure of water leaving the body is more prominent than the sum being taken in. Sicknesses of the gastrointestinal tract that cause spewing or looseness of the bowels may prompt lack of hydration. There are various different reasons for drying out including vomiting, diarrhoea, heat exposure, fiery exercise, kidney ailment and medicines that cause diuretics. Aim of the study is to know whether the people are aware of dehydration. A self developed online questionnaire was created and was completed by the participants. The questionnaire consisted of ten questions regarding the knowledge towards dehydration. The study shows that 96% of people are aware of dehydration and its health effects and have realised the need for awareness. The study concludes that most of the participants are aware of causes, symptoms and effects of dehydration. The study population has thus displayed good knowledge on dehydration and its effects.